Políticas de formação continuada de professores da rede municipal de ensino de São Paulo: o projeto formação da cidade - continuidades e descontinuidades no contexto de implementação do currículo da cidade - Silva, Gicelia Santos (2024)
The research in question presents as its object of study the City Formation Project, developed by the Department of Education of the Municipality of São Paulo, in 2022, aimed at Teachers and Pedagogical Coordinators of direct educational units, indirect and partners of the São Paulo Municipal Education Network. In this research, the analysis focuses on the introductory part of the curriculum, that is, the common part for all subjects. The question that guides the research is: What pedagogical principles and foundations guide the Continuing Training process carried out by the Municipal Department of Education of the city of São Paulo in the context of implementing the City Curriculum. The general research objective is to understand the philosophical, pedagogical and political foundations that guide the City Formation Project offered by the City of São Paulo to teachers from March 2022 to November 2022. The specific objectives are: i. analyze the City Curriculum, whose update was based on the BNCC; ii. analyze the City Formation Project of the Municipal Department of Education of the city of São Paulo, in the context of the implementation of the City Curriculum; iii. analyze the pedagogical and political philosophical foundations that guide the City Formation Project. This is a research with a qualitative approach, analyzing official documents referring to the City Training Project and the City Curriculum, legislation and bibliography, the research also includes interviews with teachers from the São Paulo Municipal Education Network, seeking to understand the process of teachers' apprehension in relation to the City Formation Project. The method of analysis was Dialectical Historical Materialism and theoretical references from authors who discuss education, such as Dermeval Saviani, Newton Duarte, Kátia Curado Silva, Luiz Carlos Freitas, Lígia Martins, among others. The research revealed a similarity between the format of the City Training Project that took place in 2022 and the initiative present in the World Bank's “Excellent Teachers” document, more specifically the in-service training of teachers verticalized and controlled by the central body. It was concluded that the City Formation Project, carried out in 2022, was based on the modern and pragmatic humanist philosophy of John Dewey, the pedagogical foundations of City Formation for teacher training were based on the line of the reflective teacher who is part of the epistemology of practice, regarding political foundations, training is part of the context of neoliberalism, centered on managerialism, monitoring and control of the pedagogical process and focused on results.